2019
DOI: 10.1016/j.ejmg.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Secondary findings from whole-exome/genome sequencing evaluating stakeholder perspectives. A review of the literature

Abstract: With the development of next generation sequencing, beyond identifying the cause of manifestations that justified prescription of the test, other information with potential interest for patients and their families, defined as secondary findings (SF), can be provided once patients have given informed consent, in particular when therapeutic and preventive options are available. The disclosure of such findings has caused much debate. The aim of this work was to summarize all opinion-based studies focusing on SF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
0
35
0
2
Order By: Relevance
“…It is thus expected, as observed here, that clinically significant variants with reduced penetrance and adult-onset conditions are detected with considerable frequency. While a majority of individuals are generally willing to receive identified actionable SF[24] and disclosure of positive results shows little to no adverse impact on participants and adds only modestly to near-term health-care costs (Hart MR 2019), the impact of reporting SF in IVF patients/gamete donors has not yet been sufficiently addressed. In 2014, a European Society of Human Reproduction and Embryology (ESHRE) task force[25] supported a broader view on preimplantation genetic testing for monogenic disease (PGT-M), including the health of third generations, which should be considered in light of recent developments in exome/genome sequencing-based PCS.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus expected, as observed here, that clinically significant variants with reduced penetrance and adult-onset conditions are detected with considerable frequency. While a majority of individuals are generally willing to receive identified actionable SF[24] and disclosure of positive results shows little to no adverse impact on participants and adds only modestly to near-term health-care costs (Hart MR 2019), the impact of reporting SF in IVF patients/gamete donors has not yet been sufficiently addressed. In 2014, a European Society of Human Reproduction and Embryology (ESHRE) task force[25] supported a broader view on preimplantation genetic testing for monogenic disease (PGT-M), including the health of third generations, which should be considered in light of recent developments in exome/genome sequencing-based PCS.…”
Section: Discussionmentioning
confidence: 99%
“…The subject of secondary findings raises a number of ethical and clinical issues. Whilst studies have shown that most key stakeholders think that both actionable and nonactionable secondary findings should be returned [11,12], healthcare professionals have acknowledged the increase in workload of clinical scientists and clinicians in interpreting and returning such results [12]. Questions have also been raised about who should consent patients and deliver test results [13].…”
Section: Introductionmentioning
confidence: 99%
“…In that case, it is quintessential for every CMG to disclose its local policy. On the other hand, and in line with the non-standardised outcome of the interaction between the clinical significance of IFs and patient characteristics, a flexibility in guidelines’ application has been advocated so they can be accustomed to the particular context [44]. Together with the professional expertise in CMGs, this call for a personalised deliberation nuances the need for and effectiveness of a rigid “one model fits all” policy [23].…”
Section: Discussionmentioning
confidence: 99%